2021
DOI: 10.1177/03000605211060197
|View full text |Cite
|
Sign up to set email alerts
|

A disease that is difficult to diagnose and treat: evaluation of 343 spondylodiscitis cases

Abstract: Objective Spondylodiscitis is an important clinical a problem requiring serious approaches. In this study, we sought to raise awareness by examining the epidemiology and laboratory, clinical, and radiological findings of spondylodiscitis, which sometimes has a delayed diagnosis and which can be difficult to treat. Methods In total, 343 patients with spondylodiscitis were included in the study. Results The patients were classified as having as pyogenic (n = 153, 44.6%), brucellar (n = 138, 40.2%), or tuberculou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Although there are differences in MRI presentation between BS and TBS, misdiagnosis often occurs because there is minimal specificity in terms of intervertebral space alteration and paravertebral abscess size. 25 27 This lack of specificity was confirmed in the present study. in the BS vs TBS(+) and BS vs TBS(−) comparisons, the MRI label-based LR model demonstrated lower AUC, upper limit of 95% CI, specificity, sensitivity, and other indicators, compared with the radiomics label-based and joint label-based RF models.…”
Section: Discussionsupporting
confidence: 85%
“…Although there are differences in MRI presentation between BS and TBS, misdiagnosis often occurs because there is minimal specificity in terms of intervertebral space alteration and paravertebral abscess size. 25 27 This lack of specificity was confirmed in the present study. in the BS vs TBS(+) and BS vs TBS(−) comparisons, the MRI label-based LR model demonstrated lower AUC, upper limit of 95% CI, specificity, sensitivity, and other indicators, compared with the radiomics label-based and joint label-based RF models.…”
Section: Discussionsupporting
confidence: 85%
“…A paraspinal abscess was found in approximately 47% of SD cases with/without epidural empyema ( 26 , 27 , 35 , 49 , 50 ). However, Chae, H. J. et al found a psoas abscess in 65% of ISEE patients ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Spondylodiscitis consists of an infection that starts within the vertebral endplates and spreads secondarily to the adjacent vertebral discs, typically manifesting in adults [ 6 ]. Spondylodiscitis differs from spondylitis, as the latter is an inflammatory condition, without any elements of infection [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spondylodiscitis differs from spondylitis, as the latter is an inflammatory condition, without any elements of infection [ 10 ]. Furthermore, spondylodiscitis can be sub-classified as pyogenic, brucellar, or tuberculous in origin, often acting as an insidious infection that requires prolonged antimicrobial therapeutic measures for successful recovery [ 6 ].…”
Section: Introductionmentioning
confidence: 99%